Dataset associated with: "Intentional mentoring should increase inclusivity in ecology" - Stuchiner, Emily; Lin Hunter, Danielle; Neuwald, Jennifer; Webb, Colleen; Balgopal, Meena (Colorado State University. Libraries, 2021)
High quality mentoring relationships can be pivotal to recruitment, retention, and long-term persistence in ecology majors and careers. The graduate-undergraduate student mentoring relationship can become uniquely important during activities like ecological fieldwork. However, graduate students often have little experience as research mentors, which can lead to negative research experiences for undergraduate mentees. Given the potential for mentoring relationships to impact people’s decisions on pursuing ecological studies and/or careers, we created and piloted a mentoring professional development program designed around intentional mentoring. Intentional mentoring requires that mentors preemptively identify what skills and knowledge their mentee should develop as well as the practices to help mentees develop these competencies. Our rationale for using intentional mentoring was that it has the potential to increase mentors’ and mentees’ awareness of issues around diversity, equity, inclusion, and social justice (DEIJ) in research experiences, in addition to developing professional competencies. To evaluate our program, we conducted focus group interviews with graduate and undergraduate student participants following a multi-week mentoring training workshop, the primary aspect of the program. Participants described an increased valuation of intentional mentoring and a desire to be more intentional in their mentoring relationships. Graduate student mentors described an increased desire to be more intentional mentors, whereas undergraduate mentees described an increased desire to seek mentors with whom they could develop intentional relationships. Undergraduates also better recognized the importance of academic mentors. Based on our evaluation, we posit that intentional mentoring can increase the retention and persistence of students with diverse identities in ecology by fostering a sense of belonging. We advocate the implementation of mentoring training workshops as a part of academic ecological programs to increase inclusion in our discipline.
Focus group interview transcripts and indications of where co-authors wrote memos while coding the dataset. These focus group transcripts are from interviews conducted in August 2019. The focus groups interviews were conducted at Colorado State University. All interviews were in accordance with IRB approval from Colorado State University.
Department of Biology
Graduate Degree Program in Ecology
Keywords: Diversity; Equity; Fieldwork; Graduate student; Inclusion; Mentoring; Professional development; Undergraduate research